ANALISIS PENGARUH GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PERBANKAN DI INDONESIA - Ika Listyawati; Ida Kristiana (MAKSIMUM, 2018)
Corporate governance is still a major problem during financial periods such as Indonesia. Especially, financial institutions  have  carried  out  reforms  to  improve  goals  and stakeholders. The purposeof this study is to measure corporate governance and in a banking environment that is specific to corporategovernance.The independent variables used in this study are ownership structures consisting of controllingshareholder ownership, foreign ownership, government ownership; the size of the board of  directors;  the sizeof the board of commissioners; independent commissioner; CAR. The sample of this study is a general bankingcompany located in Indonesia which is listed on the Indonesia Stock Exchange (BEI) for the period 2010-2014.This research data is derived  from  the  annual  report  of  the  bank  (annual  report)  for  the  period  20102014 whichis obtained fromthewebsiteof eachof the banks, theIndonesianBankingDirectory,Indonesian Capital Market Directory(ICMD).Theanalyticalmethodusedismultiple linear regression in accordance with the research objectives that analyzethe effect of independent variables on the dependentvariable. Thepurposivesamplingmethodisusedtodeterminethesampleofchoice.Fro this method,get26 samples of commercial banks.The results of the analysis found that  Controlling  Shareholder  Ownership  (OWN)  andGovernment Ownership (GOV) showed a negative relationship not significant to banking performance.However, for Foreign Ownership (FOR), Board of Directors Size  (BOD), Board  of  Commissioners  Size(BOC), Proportion of Independent Commissioners (INDEP) shows a  positive  and  significant  relationship.Then for the variable Capital Adequacy Ratio (CAR) there is a significant negative relationship.